Brief communication: Adrenal androgens and aging: Female chimpanzees (Pan troglodytes) compared with women. Issue 4 (2nd July 2013) - Blevins, James K.; Coxworth, James E.; Herndon, James G.; Hawkes, Kristen
ABSTRACT Ovarian cycling continues to similar ages in women and chimpanzees yet our nearest living cousins become decrepit during their fertile years and rarely outlive them. Given the importance of estrogen in maintaining physiological systems aside from fertility, similar ovarian aging in humans and chimpanzees combined with somatic aging differences indicates an important role for nonovarian estrogen. Consistent with this framework, researchers have nominated the adrenal androgen dehydroepiandrosterone (DHEA) and its sulfate (DHEAS), which can be peripherally converted to estrogen, as a biomarker of aging in humans and other primates. Faster decline in production of this steroid with age in chimpanzees could help explain somatic aging differences. Here, we report circulating levels of DHEAS in captive female chimpanzees and compare them with published levels in women. Instead of faster, the decline is slower in chimpanzees, but from a much lower peak. Levels reported for other great apes are lower still. These results point away from slowed decline but toward increased DHEAS production as one of the mechanisms underlying the evolution of human longevity. Am J Phys Anthropol 151:643–648, 2013. © 2013 Wiley Periodicals, Inc.